PENGARUH FACTOR FUNDAMENTAL PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN CONSUMER GOODS INDUSTRY YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013-2017 - Waode Ilsaria Weni; Buyung Sarita; Wahyuniati Hamid (Pascasarjana Universitas Halu Oleo, 2019)
This study aims to examine the effect of fundamental factors that include DER, ROE, firm size, CR, and TATO of the firm value. This study uses multiple regression analysis, the classical assumption test, F- test statistics and statistical t-test to analyze data on consumer goods industry companies listed in Indonesia stock exchange for the period 2013-2017 as many as 34 companies.The results of this study stated that DER, ROE, firm size, CR, and TATO simultaneously had an effect on PBV with an adjusted R2 value of 54.7%. While partially DER, ROE, and CR have a significant effect on the PBV, while the firm size and TATO have no significant effect on the PBV.Keywords: DER, ROE, firm size, CR, TATO, and PBV